2017
DOI: 10.7554/elife.31343
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of the NPR2 guanylyl cyclase contributes to inhibition of bone growth by fibroblast growth factor

Abstract: Activating mutations in fibroblast growth factor (FGF) receptor 3 and inactivating mutations in the NPR2 guanylyl cyclase both cause severe short stature, but how these two signaling systems interact to regulate bone growth is poorly understood. Here, we show that bone elongation is increased when NPR2 cannot be dephosphorylated and thus produces more cyclic GMP. By developing an in vivo imaging system to measure cyclic GMP production in intact tibia, we show that FGF-induced dephosphorylation of NPR2 decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…The latter might be linked to other signaling systems of which the cytoplasmic enzymes that control the phosphorylation of Npr2 are currently unknown (Schmidt and others 2018). More recently, such a link between FGFR3 signaling and the phosphorylation of Npr2 has been detected in chondrocytes (Robinson and others 2017; Shuhaibar and others 2017).…”
Section: Phosphorylation Of Npr2 and Binding Of The Ligand Cnp Are Bomentioning
confidence: 92%
“…The latter might be linked to other signaling systems of which the cytoplasmic enzymes that control the phosphorylation of Npr2 are currently unknown (Schmidt and others 2018). More recently, such a link between FGFR3 signaling and the phosphorylation of Npr2 has been detected in chondrocytes (Robinson and others 2017; Shuhaibar and others 2017).…”
Section: Phosphorylation Of Npr2 and Binding Of The Ligand Cnp Are Bomentioning
confidence: 92%
“…Although the effects of FGFR3-G380R and GC-B-7E expression on naso-anal length of mixed male and female populations have been described (10,24), the effects of sex have not been reported for either murine receptor. Using repeated measures analysis from 4 weeks to 16 weeks of age, we observed that expression of one allele of FGFR3-G380R decreased skeletal length in male mice by 4.7% but only decreased skeletal length by 1.3% in female mice compared to WT controls (Fig.…”
Section: Fgfr3-g380r and Gc-b-7e Exhibit Sex-specific Gene Dosage Effmentioning
confidence: 99%
“…Phosphorylation is absolutely required for CNP-dependent activation of GC-B and alanine substitutions for the known phosphorylation sites yields an enzyme that is not activated by CNP (15)(16)(17). In contrast, conversion of the phosphorylated serines and threonines to glutamate to constitutively mimic the negative charge of the phosphorylated residues produces an enzyme that is activated by CNP but not inactivated by dephosphorylation (20)(21)(22)(23)(24). GC-B knock out mice or GC-B mice with alanine substitutions for the phosphorylated serines and threonines are dwarfed and have smaller growth plates that are similar to those of ACH mice (17,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…LB-100 counteracts the inactivation of Npr2 by FGF in growth plate chondrocytes. NPR2 activity in chondrocytes of intact growth plates was measured as previously described, using mice expressing a FRET sensor for cGMP, cGi500 (27). The mice were WT for Fgfr3.…”
Section: Resultsmentioning
confidence: 99%